2011
DOI: 10.1371/journal.pone.0020129
|View full text |Cite
|
Sign up to set email alerts
|

Are Algae Relevant to the Detritus-Based Food Web in Tank-Bromeliads?

Abstract: We assessed the occurrence of algae in five species of tank-bromeliads found in contrasting environmental sites in a Neotropical, primary rainforest around the Nouragues Research Station, French Guiana. The distributions of both algal abundance and biomass were examined based on physical parameters, the morphological characteristics of bromeliad species and with regard to the structure of other aquatic microbial communities held in the tanks. Algae were retrieved in all of the bromeliad species with mean densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
73
1
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(80 citation statements)
references
References 48 publications
2
73
1
4
Order By: Relevance
“…Diverse communities of macro-and microorganisms inhabit these tanks and are responsible for the breakdown of tank organic matter, the release of plantavailable nutrients (Ngai and Srivastava 2006) and the emission of substantial amounts of CH 4 (Martinson et al 2010) and CO 2 (Atwood et al 2013). Tank bromeliads were used as natural model systems to study food web structures (Kitching 2001;Srivastava 2006;Srivastava et al 2008;Brouard et al 2011), animal richness (Richardson 1999), activity and distribution of (aquatic) invertebrates (Carrias et al 2001;Marino et al 2013) and microorganisms (Carmo et al 2014). Many different bacteria and archaea, which are commonly found in soils, were also detected in Ecuadorian and Costa Rican tank bromeliad slurries (Goffredi et al 2011a(Goffredi et al , 2011bMartinson et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Diverse communities of macro-and microorganisms inhabit these tanks and are responsible for the breakdown of tank organic matter, the release of plantavailable nutrients (Ngai and Srivastava 2006) and the emission of substantial amounts of CH 4 (Martinson et al 2010) and CO 2 (Atwood et al 2013). Tank bromeliads were used as natural model systems to study food web structures (Kitching 2001;Srivastava 2006;Srivastava et al 2008;Brouard et al 2011), animal richness (Richardson 1999), activity and distribution of (aquatic) invertebrates (Carrias et al 2001;Marino et al 2013) and microorganisms (Carmo et al 2014). Many different bacteria and archaea, which are commonly found in soils, were also detected in Ecuadorian and Costa Rican tank bromeliad slurries (Goffredi et al 2011a(Goffredi et al , 2011bMartinson et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Bromeliads were usually exposed to the sun, which naturally contributed for high value of that variable. Recent studies demonstrate that high sun exposure is an essential factor for the presence of algae in tank bromeliads (Brouard et al 2011, Marino et al 2011, Carrias et al 2014). ).…”
Section: Resultsmentioning
confidence: 99%
“…As an example, a few studies demonstrated that algae may be an alternative energy source for some bromeliad food webs (Brouard et al 2011, Farjalla et al 2016. Other studies have shown that different algal communities may be found in different plants that are near in the same area (Carrias et al 2014), which may be related to plant architecture (Marino et al 2011) and the exposure to sun (Sophia et al 2004, Brouard et al 2011, Carrias et al 2014, Farjalla et al 2016.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bromeliads in neotropical forests serve as habitats for bacteria (Haubrich et al 2009), algae (Brouard et al 2011), fungi (Sophia 1999), protozoa (Foissner et al 2003), arthropods and anuran amphibians (Benzing 1990, Silva et al 2011. Some invertebrates, such as oligochaetes and ostracods, spend their entire lives inside the cisterns of bromeliads (Montero et al 2010, Pinto & Jocqué 2013, while others are only found in such habitats in immature forms, mainly beetles and flies (Mestre et al 2001).…”
Section: Introductionmentioning
confidence: 99%